Nanomembranas Semicondutoras: uma nova plataforma para a investigação de fenômenos estruturais e eletrônicos - Barbara Luiza Teixeira Rosa (2018)
In this thesis we present a study of the structural and electronic properties of semiconductor heterostructures, released from their original substrate. The investigated systems were prepared with InAs quantum points grown on GaAs. Our focus is on to explore the versatility of nanomembrane manufacturing, providing new possibilities for the study of structural and electronic characteristics of epitaxially grown materials. Transmission electron microscopy (TEM), X-ray diffraction and scanning tunneling microscopy/spectroscopy (STM/S) techniques were used to investigate the islands of InAs / GaAs transferred to different substrates of interest. The study of structural properties, which makes use of the first two techniques mentioned, allowed us to directly observe anisotropic relaxation in these three-dimensional nanostructures from the statistical analysis of 164 islands observed by TEM. In addition to the completely coherent or completely relaxed islands we have observed a set of islands formed by the partial and anisotropic relaxation of the lattice parameter of the strained material, which led us to infer mechanisms of the strain relaxation processes that take place during the growth of III-V islands . The second work, in which we studied islands of InAs uncapped and capped by GaAs using STM/S, allowed the observation of energy states of the heterostructure that are compatible with those previously reported in the literature. The main advantage here is the use of an extremely simple method of sample preparation (nanomembrane), which is transferred to a Au substrate. Discrete energy levels were observed in capped islands, even with the presence of a layer of native oxide. Calculations of the energies of these levels validate the interpretation of the results obtained experimentally.